2016
DOI: 10.1080/10503307.2016.1219421
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of psychotic content in psychotherapy: An exploratory qualitative analysis of content, process, and therapist variables in a single case study

Abstract: Psychotic content may emerge in session following identifiable antecedents which change over phases of therapy. Attending to psychotic content by assuming a non-hierarchical stance and not dismissing psychotic content may aid in maintaining intersubjectivity and support patient's movements toward recovery in integrative metacognitive therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 50 publications
6
24
0
Order By: Relevance
“…Providers must then respond to consumers' unusual thoughts and experiences as potentially meaningful and not something to be treated or extinguished before understanding can be established. Thus, in the course of an interaction, the emergence of an odd belief is understood as possessing any number of potential meanings, consistent with research suggesting that symptoms do not randomly emerge, but can be tied to clear antecedents [111], and can be understood as being linked with emotional pain [112,113].…”
Section: Expert Commentarysupporting
confidence: 67%
“…Providers must then respond to consumers' unusual thoughts and experiences as potentially meaningful and not something to be treated or extinguished before understanding can be established. Thus, in the course of an interaction, the emergence of an odd belief is understood as possessing any number of potential meanings, consistent with research suggesting that symptoms do not randomly emerge, but can be tied to clear antecedents [111], and can be understood as being linked with emotional pain [112,113].…”
Section: Expert Commentarysupporting
confidence: 67%
“…In thinking about his tendencies to talk about the devil and considering past moments of acute distress, the therapist was better able to see delusional thoughts and lower levels of metacognition as protective. Consistent with observations in previous work (24), the therapist noticed that as potential vulnerability and interpersonal relatedness approached, psychotic content emerged. For instance, after a brief moment of eye contact between Geert and the therapist, it was noted that he reverted to thoughts about how the devil was instructing the psychiatrists to isolate him.…”
Section: Course Of Treatmentsupporting
confidence: 86%
“…Alternatively, perhaps medications were suboptimal, or the (metacognitive) demands put on patients during an intensive course of psychotherapy may elicit symptomatology to increase. One qualitative study into precursors of psychotic content in 48 therapy sessions revealed that particular themes of conversation could be identified before psychotic content emerged (Leonhardt et al 2016 b ) which were all related to some form of metacognitive strain. Firm conclusions are precluded given the lack of significant changes on measures of cognitive insight or illness insight in the current study.…”
Section: Discussionmentioning
confidence: 99%